Análise da expressão de genes relacionados à adipogênese e à inflamação em tecido adiposo de mulheres com obesidade grau III - Dasilio, Karine Lourenzone de Araujo (2013)
Obesity is a chronic condition defined as abnormal or excessive fat accumulation that impairs health. Overweight is an important risk factor for mortality and is a major risk factor for noncommunicable diseases, such as cardiovascular disease, impaired glucose tolerance (IGT) and type 2 diabetes mellitus (T2DM). Deposits of white adipose tissue (WAT), such as subcutaneous (SAT) and visceral (VAT), are biologically distinct, consequently, exhibited different biological effects on the health. WAT produces and secretes a variety of adipokines, such as interleukin-6 (IL-6), tumor necrosis factor-alpha (TNF-α), adiponectin (ADIPOQ), secreted frizzled-related protein 1 (SFRP1) and vascular endothelial growth factor (VEGFA), that are important in several cell functions, including angiogenesis, inflammation and adipogenesis. Alterations in adipokines expression might contribute to the onset of co-morbidities of obesity. The activation of wingless-type (WNT)/β-catenin pathway inhibits of adipogenesis via the blockade of CCAAT/enhancer binding protein alpha (CEBPA) and the peroxisome proliferator-activated receptor gamma (PPARG), which are essential transcriptional regulators of adipocyte differentiation. Evidence showed that non-fibrillar collagen XVIII (COL18A1), a protein of the extracellular matrix, has been shown to be active in adipogenesis. The aim of this study was, through quantitative Polymerase Chain Reaction, evaluate the expression of genes involved in adipogenesis and inflammation in SAT and VAT of women with severe obesity. The main results showed that i) the expression of the gene CEBPA in SAT is higher than in VAT of women with obesity ii) SAT CEBPA gene expression is higher in obese women with T2DM/IGT than in obese women with normal tolerance glucose tolerance (NGT), iii) the expression of SFRP1 gene in VAT was lower in women with T2D/IGT than those with NGT, iv) VAT COL18A1 gene expression was associated with better HDL levels and tolerance glucose. These results showed that the expression of genes involved in adipogenesis and inflammation differs in distinct WAT deposits and the expression of these genes were correlated with the metabolic parameters in obese individuals. This work contributes to a better understanding of the expression of genes related to these biological processes in SAT and VAT of patients with severe obesity.